2015
DOI: 10.1111/1468-0009.12127
|View full text |Cite
|
Sign up to set email alerts
|

Legal Protections in Public Accommodations Settings: A Critical Public Health Issue for Transgender and Gender‐Nonconforming People

Abstract: Policy Points:r Since 2012, Massachusetts law has provided legal protections against discrimination on the basis of gender identity in employment, housing, credit, public education, and hate crimes. The law does not protect against discrimination based on gender identity in public accommodations settings such as transportation, retail stores, restaurants, health care facilities, and bathrooms.r A 2013 survey of Massachusetts transgender and other gender minority adults found that in the past 12 months, 65% had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
152
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(159 citation statements)
references
References 50 publications
6
152
0
1
Order By: Relevance
“…Consistent with prior research demonstrating a significant association between prior mistreatment and avoidance of emergency and preventive care among transgender adults in Massachusetts, 3 the current national study found that avoidance of healthcare due to the fear of mistreatment was associated with healthcare refusal, suggesting that fear of mistreatment could stem from prior experiences of mistreatment. Given previous research showing that stigmatized individuals (e.g., those who have been refused care) nervously anticipate, routinely observe, and anxiously react to rejection 6 (e.g., avoid healthcare), intervention strategies are needed to address cognitive, affective, and behavioral responses to stigma among transgender people.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Consistent with prior research demonstrating a significant association between prior mistreatment and avoidance of emergency and preventive care among transgender adults in Massachusetts, 3 the current national study found that avoidance of healthcare due to the fear of mistreatment was associated with healthcare refusal, suggesting that fear of mistreatment could stem from prior experiences of mistreatment. Given previous research showing that stigmatized individuals (e.g., those who have been refused care) nervously anticipate, routinely observe, and anxiously react to rejection 6 (e.g., avoid healthcare), intervention strategies are needed to address cognitive, affective, and behavioral responses to stigma among transgender people.…”
Section: Discussionsupporting
confidence: 88%
“…2 A 2013 survey of 452 transgender people in Massachusetts found that 24% of participants had experienced verbal or physical mistreatment in a healthcare setting in the past 12 months. 3 Among this sample, mistreatment was significantly associated with avoidance of necessary medical care when sick or injured, as well as routine preventive care. The relationship between mistreatment and healthcare avoidance among transgender people has been confirmed by previous studies 4,5 and literature supports a rejection sensitivity model in which stigmatized individuals nervously anticipate (hypervigilance), routinely observe (perceived stigma), and ultimately, anxiously react to rejection (e.g., healthcare avoidance).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, even with added legal protections, transgender individuals still experience discrimination in various settings (e.g. retail, restaurants, transportation) including health care (Reisner et al, 2015) thus perpetuating barriers to receiving affirmative supports.…”
Section: Discussionmentioning
confidence: 99%
“…This confluence and intersection of oppressions, i.e., transmisogyny, potentially exacerbates mental health risk for transgender women. Indeed, surveys of diverse community samples of transgender women have documented associations between discrimination, depressive symptoms, selfesteem, and suicidal ideation (Bauer, Scheim, Pyne, Travers, & Hammond, 2015;Bockting et al, 2013;Gamarel, Reisner, Laurenceau, Nemoto, & Operario, 2014;Nemoto, Bödeker, & Iwamoto, 2011;Reisner et al, 2015). Some research has suggested that experiences of discrimination among transgender women may lead to greater HIV-risk behaviors (e.g.…”
Section: Introductionmentioning
confidence: 99%